Typical and atypical optic neuritis - Sheremet, N L; Eliseeva, D D; Kalashnikova, A K; Zakharova, M N (Vestnik oftal'mologii, 2023)
Optic neuritis (ON) is one of the most common neuro-ophthalmic causes of vision loss worldwide. Demyelinating ON can be idiopathic or be one of the symptoms of autoimmune demyelinating diseases of the central nervous system (CNS) such as multiple sclerosis (MS), neuromyelitis optica spectrum disorders (NMOSD), myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD). Demographic, clinical and radiological signs of ON in these CNS diseases have differences. In this regard, typical and atypical ON are currently distinguished. Recognizing the clinical features that differentiate typical MS-associated ON from atypical ON in NMOSD and MOGAD is important for choosing the correct disease management and treatment strategy. This review summarizes the data from clinical, laboratory, instrumental methods of management used for the differential diagnosis of optic neuritis.